Cannabidiol use and perceptions in France: a national survey - Clémence Casanova; Clémence Ramier; Davide Fortin; Patrizia Carrieri; Julien Mancini; Tangui Barré (BMC, 2022)
Abstract Background Cannabidiol (CBD), a safe, non-intoxicating cannabis component, is growing in popularity in Europe and worldwide. However, CBD EU regulation is blurry, and consequent labelling and product quality issues may have implications for public health. There is therefore a need to assess the prevalence and perceived harmfulness of CBD use in EU countries, as well as to characterise CBD users. We aimed to do so in the French population. Methods In December 2021, an online survey was conducted in a sample respecting the French adult population structure for key demographic variables. Sociodemographic, behavioural and CBD perception data were collected. Three separate regressions were performed to identify correlates of i) having heard of CBD, ii) using CBD, iii) perceived harmfulness of CBD. A hierarchical classification was also performed to identify profiles of CBD users. Results The study sample comprised 1969 adults, of whom 69.2% had heard of CBD and 10.1% used it. Less than half (46.8%) of the former considered it harmful. Having heard of CBD was associated with younger age, being born in France, tobacco use, and cannabis use. CBD use was associated with younger age, tobacco use, cannabis use, poor self-reported general health status, and positive perception of alternative medicines. Cluster analysis revealed four different CBD user profiles based on socio-demographics and behavioural characteristics. Conclusion Ten percent of the adults in this French study used CBD, and several user profiles emerged. Our results indirectly advocate clearer European CBD regulations to ensure safe and high-quality products.